Synthesis of FEEDFORWARD COMPENSATOR in the combined SYSTEM OF AUTOMATIC control WITH PID-REGULATION ON the main CHANNEL circuit - M. H. Cheikh El Najjarine; A. G. Senkov; N. N. Hurski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An automatic control system for the 1st order aperiodic object is suggested. The structural scheme includes main control circuit with a PID-regulator in it and a disturbance compensation circuit realized by two additional PID-regulators.